Engaging sexualities: Lesbian/gay print journalism, community belonging, social space and physical place - Rob Cover (Asia Pacific Network, 2005)
This artical argues that lesbian/gay print journalism publications are strategically utilised by younger readers to forge a sense of community belonging. It is shown that such publications mediate an important dynamic between self-identity and group or community identity through motifs of belonging, engagement and access. Utilising interviews with younger readers of lesbian/gay journalism, it is argued that such publications are understood by readers as a public 'social space', but that a strong desire to engage in lesbian/gay in local, geographic and physical sense is identified by the readers, suggesting that such publications perform an important but incomplete role in the construction of sexual identity and community belonging.